# Find the number of Marbles

In A, B, C are having some marbles with each of them. A has given B and C the same number of marbles each of them already have. Then, B gave C and A the same number of marbles they already have. Then C gave A and B the same number of marbles they already have. At the end A, B and C have equal number of marbles. (i) If x,y,z are the marbles initially with A,B,C respectively. Then
find the number of marbles B have at the end.

#### rakesh0814069 Profile Answers by rakesh0814069

• Aug 9th, 2010

A to B y
A to C z
A has x-(y+z)
B has 2y
C has 2z
b to A x-(y+z)
b to c 2z
B has 2y-(2z+x-y-z)
2y-z-x+y
3y-(x+z)

#### rakesh0814069 Profile Answers by rakesh0814069

• Aug 9th, 2010

step 1 a to
b=y
c=z
end a=x-(y+z)
b=2y c=2z
step 2 B to
c=2z
a=x-(y+z)
end
a=2(x-y-z)
b=2y-(2z+x-y-z)=3y-z-x
c=4z
step 3  C to
a=2(x-y-z)
b=3y-z-x
now b has=2(3y-z-x)

#### Md Parvez Profile Answers by Md Parvez

• Mar 16th, 2011

first a,b and c have same number of marbles.
a->x
b->y
c->z
now a gave b and c so
a->-x
b->y+y
c->z+z
now b gave a and c
a->-x+x
b->0
c->z+z+z
now c gave a and b
a->-x+x+x
b->0+y
c->z

it means a have x, b have y and s have z.same as they had initially.  